Long-term outcomes and late adverse effects of a prospective study on proton radiotherapy for patients with low-grade glioma. (August 2019) - Tabrizi, Shervin; Yeap, Beow Y.; Sherman, Janet C.; Nachtigall, Lisa B.; Colvin, Mary K.; Dworkin, Michael; Fullerton, Barbara C.; Daartz, Juliane; Royce, Trevor J.; Oh, Kevin S.; Batchelor, Tracy T.; Curry, William T.; et al.
Highlights: Most low-grade glioma patients retain normal neurocognitive and neuroendocrine function at 5 years after proton therapy. Most neurocognitive and neuroendocrine effects arise within 2 years of proton therapy. Neuroendocrine deficits trend with higher dose to the hypothalamus–pituitary axis. Abstract: Background: Patients with low-grade gliomas (LGG) can survive years with their illness. Proton radiotherapy (PRT) can reduce off-target dose and decrease the risk of treatment-related morbidity. We examined long-term morbidity following proton therapy in this updated prospective cohort of patients with LGG. Methods: Twenty patients with LGG were enrolled prospectively and received PRT to 54 Gy(RBE) in 30 fractions. Comprehensive baseline and longitudinal assessments of toxicity, neurocognitive and neuroendocrine function, quality of life, and survival outcomes were performed up to 5 years following treatment. Results: Six patients died (all of disease) and six had progression of disease. Median follow-up was 6.8 years for the 14 patients alive at time of reporting. Median progression-free survival (PFS) was 4.5 years. Of tumors tested for molecular markers, 71% carried the IDH1-R132H mutation and 29% had 1p/19q co-deletion. There was no overall decline in neurocognitive function; however, a subset of five patients with reported cognitive symptoms after radiation therapy had progressively worse function by neurocognitive testing. Six patients developed neuroendocrine deficiencies, five of which received Dmax ≥20 Gy(RBE) to the hypothalamus–pituitary axis (HPA). Most long-term toxicities developed within 2 years after radiation therapy. Conclusions: The majority of patients with LGG who received proton therapy retained stable cognitive and neuroendocrine function. The IDH1-R132H mutation was present in the majority, while 1p/19q loss was present in a minority. A subset of patients developed neuroendocrine deficiencies and was more common in those with higher dose to the HPA.